55.7k views
5 votes
Does anybody know this ... dang ...

Does anybody know this ... dang ...-example-1
User Ashawn
by
5.3k points

1 Answer

6 votes

Answer: (6, -6)

Explanation:

so midpoint =(
(X1+X2)/(2),
(Y1+Y2)/(2))

for x co ordinate


(-2+X2)/(2)=2

-2+X=4 (X2=x co ordinate point for b, can be written as just x now)

X=6

x co ordinate of B= 6

y co ordinates of y


(-8+Y2)/(2)=-7

-8+Y=-14

Y=-6

co ordinates B (6,-6)

for proof/extra explanation (NOT necessary for working):


(Y1+Y2)/(2)

=
((-2)+6, (-8)+(-6))/(2)

=
(4, -14)/(2)

=(2,-7)

which is the midpoint M

User Azher Aleem
by
5.7k points